Employee Engagement -A review of contemporary thinking from business perspective (International Journal of Food and Nutritional Sciences, 2022)
The main aim of the present research paper is to understand employee engagement in Human Resource Management and to organize literature review on employee engagement concept which is frequently used in HRM. Creating the engagement plan will help management to leverage financial aspects and to engage their employees in a better manner as well as becoming more engaged themselves. Researching engagements prior to creating the engagement plan helped to identify potential resources to utilize in the plan. This review provides simplicity on the meaning of employee engagement and how managers can apply this research to their employees‟ engagements. This initial literature review helped to articulate meaning, definitions and possible outcomes of employee engagement view. The study focuses on the concept of Employee Engagement (EE) and how that concept is twisted to use in business houses from management perspective. This paper is based on secondary data. The data and information is collected from different books, journals and websites. The study can be eye opener for understanding idea of Employee Engagement to achieve business goals and objectives.